Diseño y Layout de la distribución de almacenaje para el centro de distribución de decorceramicas S.A.S en Barranquilla (Producto: Porcelanato y Cerámica) (2013)
Our Project is based on the research of the best way to perform a design and layout applied to the warehouse of Decorceramica located on Barranquilla City and which is beginning with their activities. The Challenge is to overcome the startup of this distribution centre. For this, we have to consider that a empty warehouse initialy has to be supplied the sooner possible to begin to be operative, what means that is necessary to be prepared in how the merchandise will be accommodated, in a way the production from this CEDI to be the most productive possible, not just the packaging but in the resources that will be invested to achieve the objectives, being the most important to achieve a optimal costumer service to our internal and external costumers, empathizing on the final users. This project was framed in the type "projective research", founded to an understandable level with a design of mix source (documental and field). There was implemented a series of techniques and instruments of data recollection, specifically the analysis of documental sources, direct observation, and unstructured interviews. For the realization of the design and layout, as for the startup, we used information form de contributions of studies made form intellectuals and mainly from the theories of eng. Richard Muther and eng. Our Project is based on the research of the best way to perform a design and layout applied to the warehouse of Decorceramica located on Barranquilla City and which is beginning with their activities. The Challenge is to overcome the startup of this distribution centre. For this, we have to consider that a empty warehouse initialy has to be supplied the sooner possible to begin to be operative, what means that is necessary to be prepared in how the merchandise will be accommodated, in a way the production from this CEDI to be the most productive possible, not just the packaging but in the resources that will be invested to achieve the objectives, being the most important to achieve a optimal costumer service to our internal and external costumers, empathizing on the final users. This project was framed in the type "projective research", founded to an understandable level with a design of mix source (documental and field). There was implemented a series of techniques and instruments of data recollection, specifically the analysis of documental sources, direct observation, and unstructured interviews. For the realization of the design and layout, as for the startup, we used information form de contributions of studies made form intellectuals and mainly from the theories of eng. Richard Muther and eng. Bryan Salazar, besides from the valuable data supplied by Decorceramica for the realization of it. In the end we could conclude with an approach that guarantees the best use for the space available, the optimization of the resources and besides contributes with the improvement of the service level.